Etos Kerja Ilahi Dalam Kitab Amsal: Analisis Eksegetis Ḥarūṣ dan ‘āṣēl Untuk Etika Praktis Modern - Supriyatin (STT INTI Bandung, 2025)
This study offers an exegetical analysis of the contrast between diligence (ḥarūṣ) and laziness (‘āṣēl) in the Book of Proverbs to uncover the underlying divine work ethic. By comparing the Masoretic Text (MT) and the Septuagint (LXX) through qualitative and intertextual methods, this research demonstrates that the choice between ḥarūṣ and ‘āṣēl reflects a moral and spiritual decision rooted in divine wisdom. The findings indicate that laziness (‘āṣēl), rendered as oknērós (hesitant/sluggish) in the LXX, constitutes a sin of the heart grounded in unbelief and a rejection of the Imago Dei, resulting in spiritual emptiness and material ruin. Conversely, diligence (ḥarūṣ) represents an act of obedience and worship that leads to shalom (wholeness and soul-satisfaction). Ethically, this divine work ethic challenges modern believers to embrace holistic productivity while rejecting both workaholism (as the idolization of economic achievement) and chronic laziness (quiet quitting). In conclusion, Proverbs calls believers to view work as a sacred vocation and a means of character formation, making it a vital ethical witness to the modern world.